ANALISIS PENERAPAN MODEL PEMBELAJARAN POE2WE BERBASIS HANDS ON ACTIVITY TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Mubarok, Ilham; Nana, Nana; Sulistyaningsih, Dwi (EduFisika: Jurnal Pendidikan Fisika, 2020)
The POE2WE learning model is a learning model developed to determine students' understanding of a concept with a constructivist approach. Hands on activity is an activity designed to involve students in seeking information and asking questions, doing activities and finding, collecting data and analyzing, and making their own conclusions. The purpose of this study was to analyze the application of the hand on activity-based POE2WE model to critical thinking skills. This research uses literature study method. The research was conducted by collecting secondary data from articles relevant to the topic under study. The data were analyzed and concluded. The results of the synthesis of relevant research indicate that the Hands On Activity learning model is effective for critical thinking and is active in social interaction. In addition, POE2WE learning will make it easier for teachers by involving students to be more active, and reflecting on new understandings according to the initial knowledge possessed by students.